Surface properties of non-conventional cellulose fibres. (2019) - Smole, Majda Sfiligoj; Hribernik, Silvo; Kurečič, Manja; Krajnc, Anja Urbanek; Kreže, Tatjana; Kleinschek, Karin Stana
No abstract available